Law Enforcement Of Narcotics Laws - Asep Iswahyudi Rachman; Sri Kusriyah (Law Development Journal, 2020)
This study aims to explore the law enforcement of the Republic of Indonesia Act No. 35 of 2009 on Narcotics by the Directorate of Drug Research at the Central Java Regional Police. An empirical juridical approach is used to study the phenomena that are the focus of research. Data collection techniques using data reduction, data presentation, triangulation and drawing conclusions. The results showed that the narcotics crime in the jurisdiction of the Central Java Regional Police was already at an unsettling stage and not only involved the adult group, but also touched teenagers and children. Law enforcement of Act No. 35 of 2009 concerning Narcotics" by the Central Java Regional Police's Narcotics Research Directorate is carried out by penal and non-penal. In the effort to enforce the law enforcement by means of the implementation of the Narcotics Law, there are still problems related to "defining the Chapter General Provisions of Act No. 35 of 2009 concerning" Narcotics. In defining "in the Chapter General Provisions of Act No. 35 of 2009 concerning Narcotics in its implementation it has an impact on the handling of narcotics addicts, narcotics abuse and victims of narcotics abuse with the dealers or dealers" of narcotics. The inhibiting factors in enforcing Act No. 35 of 2009 concerning Narcotics by" the Directorate of Drug Research at the Central Java Regional Police are the imbalance in the number of personnel / resources of the Central Java Regional Police's Narcotics Diresnarkoba with inadequate areas, facilities and infrastructure, especially technology-related facilities. (IT), and most importantly the low level of public awareness of the dangers of narcotics.